Post-traumatic stress disorder among military personnel admitted at the Northwest Command Level Three Military Hospital, Bahir Dar, Ethiopia, 2022: an institution-based cross-sectional study - Tedla, Assasahegn; Asnakew, Sintayehu; Legas, Getasew; Munie, Birhanu Mengist; Tareke, Minale; Beka, Micheal (Frontiers in Psychiatry, 2024)
Background: -Post-traumatic stress disorder (PTSD) is one of the most common mental health problems that military personnel encounter. It could be life-long and affect every aspect of military personnel, including their mental and physical health, family and social interactions, and their work. However, in Ethiopia, the magnitude and its associated factors have not been well investigated.Objective: This study aimed to determine the prevalence of post-traumatic stress disorder and its associated factors among military personnel, who were admitted to Northwest Command level three military Hospitals,